Haem-dependent dimerization of PGRMC1/Sigma-2 receptor facilitates cancer proliferation and chemoresistance - Kabe, Yasuaki; Nakane, Takanori; Koike, Ikko; Yamamoto, Tatsuya; Sugiura, Yuki; Harada, Erisa; Sugase, Kenji; Shimamura, Tatsuro; Ohmura, Mitsuyo; Muraoka, Kazumi; Yamamoto, Ayumi; Uchida, Takeshi; et al. (Nature communications, 2016)
Progesterone-receptor membrane component 1 (PGRMC1/Sigma-2 receptor) is a haem-containing protein that interacts with epidermal growth factor receptor (EGFR) and cytochromes P450 to regulate cancer proliferation and chemoresistance; its structural basis remains unknown. Here crystallographic analyses of the PGRMC1 cytosolic domain at 1.95 Å resolution reveal that it forms a stable dimer through stacking interactions of two protruding haem molecules. The haem iron is five-coordinated by Tyr113, and the open surface of the haem mediates dimerization. Carbon monoxide (CO) interferes with PGRMC1 dimerization by binding to the sixth coordination site of the haem. Haem-mediated PGRMC1 dimerization is required for interactions with EGFR and cytochromes P450, cancer proliferation and chemoresistance against anti-cancer drugs; these events are attenuated by either CO or haem deprivation in cancer cells. This study demonstrates protein dimerization via haem–haem stacking, which has not been seen in eukaryotes, and provides insights into its functional significance in cancer. PGRMC1 binds to EGFR and cytochromes P450, and is known to be involved in cancer proliferation and in drug resistance. Here, the authors determine the structure of the cytosolic domain of PGRMC1, which forms a dimer via haem–haem stacking, and propose how this interaction could be involved in its function.